2020
DOI: 10.1017/s0022215120001036
|View full text |Cite
|
Sign up to set email alerts
|

Inner-ear malformations as a cause of single-sided deafness

Abstract: AbstractObjectiveTo determine the prevalence and distribution of inner-ear malformations in congenital single-sided deafness cases, as details of malformation type are crucial for disease prognosis and management.MethodsA retrospective study was conducted of 90 patients aged under 16 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…CND was demonstrated in 29.9% of ears in the UHL population, which is within the reported range in the literature. However, this is slightly below the median previously reported in the literature, with 5 of the 8 cited studies reporting nerve deficiency in 39-50% of ears [Clemmens et al, 2013;Nakano et al, 2013;Paul et al, 2017;Usami et al, 2017;van Beeck Calkoen et al, 2017;Lipschitz et al, 2020;Pollaers et al, 2020;Tahir et al, 2020]. In contrast to the UHL cohort, CND was found in a significantly lower proportion of ears in the AHL population (11.5%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…CND was demonstrated in 29.9% of ears in the UHL population, which is within the reported range in the literature. However, this is slightly below the median previously reported in the literature, with 5 of the 8 cited studies reporting nerve deficiency in 39-50% of ears [Clemmens et al, 2013;Nakano et al, 2013;Paul et al, 2017;Usami et al, 2017;van Beeck Calkoen et al, 2017;Lipschitz et al, 2020;Pollaers et al, 2020;Tahir et al, 2020]. In contrast to the UHL cohort, CND was found in a significantly lower proportion of ears in the AHL population (11.5%).…”
Section: Discussionmentioning
confidence: 76%
“…While several past studies have evaluated CND in pediatric patients with UHL, the literature has reported widely variable prevalence of CND ranging from 9 to 50% [Clemmens et al, 2013;Nakano et al, 2013;Paul et al, 2017;Usami et al, 2017;van Beeck Calkoen et al, 2017;Lipschitz et al, 2020;Pollaers et al, 2020;Tahir et al, 2020]. Evaluation of CND in pediatric patients with AHL has been limited in the literature, with studies reporting a range of 0-28% prevalence of CND [Usami et al, 2017;Lipschitz et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhan et al 28 reported that MRI imaging was their first choice in children, and if MRI findings were not optimal, they used temporal bone CT as an adjunct. Tahir et al 32 reported that they generally preferred CT + MRI together as imaging for children with a diagnosis of SSD but recently stated that to reduce radiation exposure, they prefer only MRI for children for whom surgery is not considered. 32 While CT is useful for the diagnosis of middle and inner ear anomalies (partition anomalies and common cavity), MRI is a standard diagnostic tool to detect the absence of the cochlear nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Tahir et al 32 reported that they generally preferred CT + MRI together as imaging for children with a diagnosis of SSD but recently stated that to reduce radiation exposure, they prefer only MRI for children for whom surgery is not considered. 32 While CT is useful for the diagnosis of middle and inner ear anomalies (partition anomalies and common cavity), MRI is a standard diagnostic tool to detect the absence of the cochlear nerve. Therefore, Park et al 33 recommend high-resolution 3-dimensional MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A cochlear nerve deficiency was the most frequent MRI finding. We prefer to use this term because the difference between hypoplasia and aplasia is not always evident, and cochlear aperture width and cochlear nerve status do not always correlate (24). Cochlear nerve deficiency has been found in about 30% of the patients with congenital sensorineural hearing loss and accounts for even a higher percentage in the group of severe to profound hearing loss (13,25).…”
Section: Discussionmentioning
confidence: 99%